Numerical Simulation of the Aerodynamic Characteristics of NACA0012 Airfoil Based on Operational Parameters - Mula, Ayat A.; Abdulwahid, Mohammed A. (Basrah Journal for Engineering Sciences, 2023)
This study investigated the performance of symmetric airfoils of type NACA0012 numerically under different operating conditions. It has been assumed that the study involves steady state, non-compressive, and turbulent flows. The operating fluid was air. The effect of Reynolds number and angle of attack on lift and drag coefficients, pressure distribution, and velocity distribution was investigated. ANSYS FLUENT has been used to solve the numerical model by using continuity equations, Navier-Stokes equations, and the appropriate K-ω SST perturbation model. This study shows a clear difference between the pressure coefficient of the lower and upper surfaces of the airfoil at high Reynolds numbers, indicating higher lift at high Reynolds numbers. As the maximum stall angle of the airfoil NACA0012 is 14° after which it decreases significantly, a direct relationship was observed between lift and drag coefficients and angle of attack.